Construction of a genome-scale structural map at single-nucleotide resolution - Greenbaum, Jason A.; Pang, Bo; Tullius, Thomas D. (Genome Research, 2007)
Few methods are available for mapping the local structure of DNA throughout a genome. The hydroxyl radical cleavage pattern is a measure of the local variation in solvent-accessible surface area of duplex DNA, and thus provides information on the local shape and structure of DNA. We report the construction of a relational database, ORChID (OH Radical Cleavage Intensity Database), that contains extensive hydroxyl radical cleavage data produced from two DNA libraries. We have used the ORChID database to develop a set of algorithms that are capable of predicting the hydroxyl radical cleavage pattern of a DNA sequence of essentially any length, to high accuracy. We have used the prediction algorithm to produce a structural map of the 30 Mb of the ENCODE regions of the human genome.